Postsynaptic clustering of γ-aminobutyric acid type A receptors by the γ3 subunit in vivo - Baer, Kristin (The National Academy of Sciences, 1999)
Synaptic localization of γ-aminobutyric acid type A (GABA(A)) receptors is a prerequisite for synaptic inhibitory function, but the mechanism by which different receptor subtypes are localized to postsynaptic sites is poorly understood. The γ2 subunit and the postsynaptic clustering protein gephyrin are required for synaptic localization and function of major GABA(A) receptor subtypes. We now show that transgenic overexpression of the γ3 subunit in γ2 subunit-deficient mice restores benzodiazepine binding sites, benzodiazepine-modulated whole cell currents, and postsynaptic miniature currents, suggesting the formation of functional, postsynaptic receptors. Moreover, the γ3 subunit can substitute for γ2 in the formation of GABA(A) receptors that are synaptically clustered and colocalized with gephyrin in vivo. These clusters were formed even in brain regions devoid of endogenous γ3 subunit, indicating that the factors present for clustering of γ2 subunit-containing receptors are sufficient to cluster γ3 subunit-containing receptors. The GABA(A) receptor and gephyrin-clustering properties of the ectopic γ3 subunit were also observed for the endogenous γ3 subunit, but only in the absence of the γ2 subunit, suggesting that the γ3 subunit is at a competitive disadvantage with the γ2 subunit for clustering of postsynaptic GABA(A) receptors in wild-type mice.